PERANCANGAN VIDEO ADVERTORIAL MUSEUM KERIS NUSANTARA SURAKARTA - Indra Hayu Tri Pamungkas; Ahmad Khoirul Anwar; Evelyn Henny Lukitasari (Akademi Seni dan Desain Indonesia Surakarta, 2024)
Keris Nusantara Museum is one of the museums in the city of Surakarta. This museum holds a lot of historical objects such as keris and spears. Not only does it store historical objects, but this museum also contains lessons about the history, manufacture and story behind the keris itself. This place is great for people who love history. Currently, the interest in the Indonesian Keris Museum is slightly declining because many people prefer to go to modern shopping centers to spend their free time, rather than visiting and studying the history of the past. Therefore, a media was created for the promotional event for the Keris Nusanara Museum. The title of this research is